English Color Idioms and Arabic Color Idioms - Israa B. Azeez; Marjan ‎ Abbasian; Huda Y. Abdulwahid (Cihan University-Erbil Journal of Humanities and Social Sciences, 2023)
This study is an attempt to make a comparative study between Arabic and English regarding color idioms. It tends to make a comparison by shedding light on similarities between Arabic and English regarding Color idioms. Eighteen color idioms have been chosen; ten from English and nine from Arabic. Each idiom has been analyzed literally (dictionary meaning) and non-literally (figurative meaning).  The analysis has displayed that both languages share some common connotations and literal meanings for a number of idioms.  It has showed some differences as well.  It can be drawn that although these languages are aliens, descending from two various origins, yet they share some meanings. Besides, the analysis has explored that some idioms might have more than one meaning depending on the context.  As a last point, the meaning of these color idioms may differ according to culture, language, customs and traditions, religion, and situations.